Fertilizer effects on the quality and production of prickly pear cactus and its wildlife value - Gonzalez, C. L.; Everitt, J. H. (Journal of the Professional Association for Cactus Development, 1990)
Prickly pear cactus (Opuntia lindheimeri E.) is an abundant plant in South Texas and notheastern Mexico. The Rio Grande Plain, also known as the Texas brush country, probably has the highest populations of prickly pear. Heavy infestations of prickly pear also extended to west-central Texas. Prickly pear is a drought-resistant, hardy plant.